Quantitative analysis of catechins in Saraca asoca and correlation with antimicrobial activity - Amey Shirolkar; Anjum Gahlaut; Anil K. Chhillar; Rajesh Dabur (Elsevier, 2013)
Herbal medicines are highly complex and have unknown mechanisms in diseases treatment. Saraca asoca (Roxb.), De. Wild has been recommended to treat gynecological disorders and used in several commercial polyherbal formulations. In present study, efforts have been made to explore antimicrobial activity and its co-relation with the distributions of catechins in the organs of S. asoca using targeted MS/MS. Eight extracts (cold and hot water) from four different organs of S. asoca and two drugs were prepared and antimicrobial activity was assessed by microbroth dilution assay. Quantitative and qualitative analysis of catechins in crude extracts was done by using targeted and auto-MS/MS and correlated with antimicrobial activity. (+)-Catechin and (+)-epicatechin and their biosynthesis related compound were found to be up-regulated in regenerated bark and leaves extracts. (â)-Epigallocatechin was found to be significantly higher in bark water extract as compared to others but showed low antimicrobial activity. Result showed down-regulation of (â)-epigallocatechin and up-regulation of (+)-catechin and (+)-epicatechin in the regenerated bark and leaves of S. asoca. It might be the contributing factor in the antimicrobial activity of regenerated bark and leaves of the plant. The concentration of (+)-epicatechin in processed drugs (Ashokarishta) from Baidyanath was found to be seven times higher than that of Dabur Pvt. Ltd., but no antimicrobial activity was observed, indicating the variations among the plant based drugs. This will be helpful in rational use of S. asoca parts. Furthermore, the analytical method developed is sensitive, repeatable and reliable; therefore, it is suitable for quality control of herbal drugs. Keywords: Mass spectroscopy, Phytochemistry, Quality control, Flavonoids, Ayurveda, Antimicrobial